Enantioselective theranostics of brain glioma using chiral quantum structures. (February 2023) - Hao, Junjie; Hu, Die; Chen, Peixian; Ma, Liu; Xia, Miao; Chen, Meijuan; Xu, Hefeng; Liu, Hanmeng; Li, Yiwen; Cheng, Jiaji; Jin, Xue; Duan, Pengfei; et al.
Graphical abstract: Circularly polarized light responsive biological theranostics in brain glioma was realized via using chiral CdSe/CdS dot-in-rods which play as efficient candidates for high-quality bioimaging and enatioselectively stimulate the generation of enhanced oxygen species and hydroxyl radical, providing synergistic therapy in glioma cells with more than 3.14 times higher efficacy compared to normal phototherapy without chiral selection. Highlights: Cysteine capped CdSe/CdS dot-in-rods (DRs) have satisfied biocompatibility for high-quality bioimaging and phototherapy. Chiral CdSe/CdS DRs enatioselectively stimulate the generation of reactive oxygen species and hydroxyl radical (OH). Synergistic therapy in glioma cells can be achieved with greater than 3.14 times higher efficacy compared to normal phototherapy. Infiltrative growth and metastasis of glioma cells is reduced nearly 50 %. Abstract: CdSe/CdS dot-in-rods (DRs) tailored by chiral biomolecules are promising candidates for biological theranostics. The authors of this study synthesised chiral CdSe/CdS DRs with different sizes using the post-ligand-exchange method. Their high-resolution imaging and cytotoxicity performances were investigated, respectively. The results suggested that the chiral cysteine coverage strategy could significantly enhance the biocompatibility of CdSe/CdS DRs in bioimaging and bioimaging-guided therapies. Numerous photodynamic and chemodynamic therapy studies for brain glioma cells demonstrated enantioselective efficacy, wherein chiral DRs could exhibit improved oxygen species and hydroxyl radical generations under corresponding circularly polarised light radiation. d -DRs with right-handed circularly polarised light activation could generally present 3.14/1.5 times higher efficacy than left-handed or linearly polarised light irradiated samples. Wound-healing assay/migration and invasion assays asserted that the applications of chiral DRs could suppress the infiltrative growth and metastasis of glioma cells by reducing the migration and invasion ability by nearly 50%. In vivo experiments also confirmed that d -DRs exerted more substantial enhanced permeability and retention (EPR) effects in the tumour tissue, leading to better bioimaging ability and efficient tumour ablation. Such adjuvant approaches would be a viable alternative to cancer treatments with a high possibility of recurrence and poor prognosis.